The current state and prospects for the development of the Ukrainian market of veterinary drugs for the treatment of skin diseases - I. V. Bushuieva; M. V. Ohloblina (Zaporozhye State Medical University, 2023)
The trend of increasing incidence of skin diseases of various etiologies and the frequency of complications caused by them (dermatitis, allergies, secondary infections, eczema, trichophytosis, dermatophytosis, dermatomycosis, etc.) is increasing in Ukraine. Nowadays the important problem is the development of new domestic effective medicines to combat this pathology. The general market of veterinary drugs, feed additives of finished feed, and premixes was investigated, and the place of drugs used to combat fungal diseases of animal skin was determined to identify the current state and prospects for the development of domestic veterinary drugs (DVD) production. It is established that the studied range of the market saturation structure of veterinary drugs, feed additives, finished feeds, and premixes have significant competition in the pharmaceutical market of Ukraine from foreign manufacturers. The range of effective domestic medicines for the treatment of fungal skin diseases of animals based on domestic substances is very minor, so there are prospects for the introduction into production and further promotion of new effective drugs in this area on the domestic market. The aim of the work is to determine the current state and prospects for the development of the production of national veterinary medicines for the treatment of fungal diseases of animal skin based on the study of the structure of the general market for veterinary drugs, feed additives, finished feed, premixes and determination of their market share. Materials and methods. The following methods (synthetic, analytical, information search, descriptive, generalization) were used in the work. The research materials were literary sources that contain information on the structure of the veterinary market of antifungal and antimicrobial drugs and the "List of Registration of Veterinary Drugs, Feed Additives, and Finished Feeds" as of July 21, 2022. Results. According to the above List, it was found that as of 21.07.2022, 6574 trade names of these products were registered on the Ukrainian market of veterinary medicines, feed additives, finished feed, and premixes. 5097 (77.53 %) of which were supplied by foreign manufacturers, the rest - 1497 (22.47 %) were products of domestic manufacturers. The geography of suppliers is represented by 47 countries, including Ukraine. France, Poland, and Germany remain the leaders in terms of the number of registered items of drugs, feed additives, finished feeds, and premixes. Based on the marketing analysis, it was found that in terms of dosage forms, this market is overly heterogeneous and is represented by 31 dosage forms, which are powders, liquid, solid, soft, and gaseous forms by consistency. It has been proved that a small assortment of antifungal DVDs makes it possible to saturate this segment of the pharmaceutical market not only with imported drugs, but also to find opportunities for the creation and introduction of fundamentally new antifungal DVDs to the domestic market. Conclusions. The development and introduction of new antifungal drugs to the market for further use in the treatment of skin diseases are important. It will contribute to improving the effectiveness of prevention and treatment of the above diseases and will allow the offering of effective innovative pharmacotherapeutic drugs to domestic veterinary practice.